2015
DOI: 10.1080/02508060.2015.1094617
|View full text |Cite
|
Sign up to set email alerts
|

The impact of water users’ associations on the productivity of irrigated agriculture in Pakistani Punjab

Abstract: The government of Pakistan has been involved in the transfer of irrigation management to farmers' organizations at different levels of irrigation networks. Khal Panchayats or water users' associations are mandated to mediate water distribution conflicts, maintain watercourses, report on tampering of outlets and shortage of water supply in the outlet to minor or distributary-level farmer organizations, collect water charges, and provide timely information about rotational running of channels to the farmers. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Even after PIM/IMT, many WUAs remain trapped in a vicious circle of "insufficient maintenance-downgrading infrastructure-poor performance-low-cost recovery" [11]. Cases of this vicious circle have been documented in Tunisia and Pakistan [31,33]. WUAs have been reported to approve deficit budgets to match farmers' willingness to pay.…”
Section: Inadequate Wua Cost Recoverymentioning
confidence: 99%
“…Even after PIM/IMT, many WUAs remain trapped in a vicious circle of "insufficient maintenance-downgrading infrastructure-poor performance-low-cost recovery" [11]. Cases of this vicious circle have been documented in Tunisia and Pakistan [31,33]. WUAs have been reported to approve deficit budgets to match farmers' willingness to pay.…”
Section: Inadequate Wua Cost Recoverymentioning
confidence: 99%
“…Interdependence of different sectors at different scales can cause unintended trade-offs or support synergistic activities. Mekonnen et al (2015) find productivity-enhancing effects of water users' associations in Pakistani Punjab for farmers who rely on groundwater and are thus not in the remit of watercourse water users' associations. The article concludes that improving the management of surface water through functioning watercourse-level institutions can be a viable option for reducing over-utilization of groundwater resources and the pressure it creates on the already strained energy situation in Pakistan.…”
Section: Governance Of the Nexusmentioning
confidence: 89%
“…Such institutions include river basin organizations at the basin or watershed level, water user associations at the level of irrigation systems, and community rules or regulations for using shared aquifer resources. Mekonnen, Channa, and Ringler (2015) found that the existence of effective water user organizations improved agricultural productivity of farmers at the tail end of irrigation canals. At the community level, pilot studies in India have shown that collective groundwater management facilitated by experimental games can be effective in improving local groundwater governance (Meinzen-Dick et al 2018).…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%